A Review of the Role of Chronic Traumatic Encephalopathy in Criminal Court - Aaronson, Alexandra L.; Bordelon, Sean D.; Brakel, S. Jan; Morrison, Helen (Journal of the American Academy of Psychiatry and the Law Online, 2021)
Chronic traumatic encephalopathy (CTE) is believed to be a degenerative brain disease characterized by repetitive brain trauma resulting in a specific pattern of neuropathological changes, which some have linked to functional disturbance and aggression. The diagnosis has gained greater public attention after these same neuropathological changes were discovered in multiple deceased National Football League (NFL) players, many of whom had exhibited signs of aggression, impulsivity, and poor executive functioning, according to a widely publicized study. When an NFL player convicted of murder was found to have the neuropathological changes associated with CTE following his suicide, the New York Times editorial section asked whether CTE was a defense for murder. This idea raises an interesting legal and philosophical question about whether an individual's criminal actions can be determined by something outside their control, such as past head trauma. To begin to attempt an answer, this article reviews what is currently known about the neurobiology of traumatic brain injury, CTE, and morality. By looking at how U.S. criminal law courts have handled cases of dementia and traumatic brain injury in the past, we can better understand how to consider this postmortem diagnosis in its forensic context.